Characteristics and optimization of dairy manure composting for reuse as a dairy mattress in areas with large temperature differences. (20th September 2019) - Zhang, Qiuping; Liu, Jianguo; Guo, Haobo; Li, Enrui; Yan, Yaping
Abstract: Aerobic composting of dairy manure for reuse as cow mattress is an efficient and environmentally friendly technology. Herein, composting including the mesophilic and thermophilic stage without cooling and maturation was studied in different seasons using dairy manure as a substrate considering the characteristics of areas with large temperature differences. Composting was completed during spring and summer under natural conditions, but not during autumn and winter. At sub-low temperature (i.e. −10–15 °C), adjusting the turning frequency, straw, and microbial inoculum addition was performed to optimize the composting. A dairy manure/straw ratio of 2:1 (v:v), 4 days of turns, and addition of 1.3 L/t microbial inoculum were optimal for rapid warming and long thermophilic stage duration. After composting, the water content was approximately 50% and polymerase chain reaction-denaturing gradient gel electrophoresis (PCR-DGGE) analysis showed that the microbial community structure of the composted samples differed greatly between seasons. The dominant bacteria belonged to the genera Clostridium and Flavobacterium . Quantitative PCR showed that four common pathogenic bacteria, Salmonella, Shigella, Staphylococcus aureus, and Escherichia coli, were not present after composting, indicating that pathogenic bacteria could be inactivated by dairy manure composting. The composted products satisfied harmlessness and hygienic standards for reuse as a dairy mattress. Graphical abstract: Image 1 Highlights: It is clean and safety to reuse dairy manure composting products as mattress. Aerobic composting can be completed by adjusting process parameters. The dominant bacteria during composting were Clostridium and Flavobacterium. The pathogens were inactivated by composting.